EVALUATION OF SEEPAGE LOSSES IN AN EARTH LINED CANAL: A CASE STUDY OF UNIVERSITY OF UYO FARM, UYO, NIGERIA. (International Journal of Engineering Sciences & Management Research, 2015)
The research farm of the department of Agricultural Engineering, University of Uyo was the study area. The purpose of the study was to evaluate seepage losses in an earth lined canal. The research was carried out on two different canals located at about 30m apart. A prior analysis of some properties of the liners and soil sample from the canal was carried out in the soil mechanics laboratory of the University. These include: particle size distribution and soil texture, soil classification, moisture content, soil hydraulic conductivity and Atterberg’’s limits. Experiment on the seepage losses was conducted on a 5m long, 1m width and 1m deep canals, with only 0.6m depth of canal lined with mixture of 7 headpands (175kg) of clay and 2kg of bentonite. Water was filled to only 0.6m out of the 1m depth of the canal. Ponding method was used to measure the volume of water lost through seepage taking account of losses due to evaporation while other losses from discharge devices were not accounted for. Average seepage losses of 0.29m3/hour and 0.05m3/hour were obtained for the unlined and lined canals respectively. The study recommends that the mixture of clay and bentonite in the proportion stated be used by small and medium scale farmers who wish to control seepage losses with a moisture saving capacity of 82.8% within study area.